Vertical force requirement for stump lifting - I. Czupy; E. Horváth-Szováti (Journal of Forest Science, 2013)
In harvest areas the soil preparation is occasionally necessary before reforestation including the removal, collection and transportation of stumps from the soil. Issues related to climate change and the shortage of fossil energy sources call for an increased rate of renewable energy sources. Using the stumps removed from the soil as fuel is a significant resource for biomass. For lifting a stump together with its roots a grab mounted on a shovel is generally used. To rationalise this operation, analyses of stump lifting time have been carried out. We tested a machine mounting one grab for stump lifting on three tree types (Scots pine, robinia and poplar) and found functions correlating stump extraction force and stump diameter, which can be used in order to choose the right machine and determine the cost of the operation.